Site-directed allostery perturbation to probe the negative regulation of hypoxia inducible factor-1α - Petrovicz Vencel László (RSC CHEMICAL BIOLOGY, 2024)
The interaction between the intrinsically disordered transcription factor HIF-1α and the coactivator proteins p300/CBP is essential in the fast response to low oxygenation. The negative feedback regulator, CITED2, switches off...